Centralized Database: A Prerequisite for Security and Sustainable Development in Nigeria (International Journal of Innovative Research in Computer Science & Technology, 2017)
The volume of data organizations and government  agencies usually collect and store are increasing rapidly.  Centralized database according to Elmasri and Navathe [1] stores data or information in a particular location within a  network. It allows data from existing database to be  collected and stored in a single database for sharing,  analysis or updating in an organisation. In Nigeria,  organizations and government agencies usually operates  distributed databases and do not have a centralised database  in a central location for sharing and other policy making.  Therefore, this paper highlights the need for centralised  database that can be adopted by government to control data  redundancy and inconsistency for security and sustainable  development. The paper is a survey paper that explored the  use of research schedules for data collection.  Enumeratorwas picked from each of the four agencies that  constitutes the population and samples of the study. The  data collected were categorised and presented based on the  research schedules retrieved. The results show the common  fields used on personal information of individuals as ID,  names, Date of Birth, Gender, address, phone no, finger  print, and photograph. The results also show that data  sharing among agencies are rarely done using the  distributed databases, but plans are on the way to actualize  that especially with the yet-to-be implemented model of  National Identity Management Commission known as  National Identity Management System (NIMS). Finally, the  paper recommends that government should explore the  possibility of adopting centralised database that can  harmonise records of organisations and agencieswhich will  help in ensuring security and sustainable development in the  country; a model of centralised database should be designed  to ascertain the feasibility of implementing a centralised  database in Nigeria; thorough research should also be made  to ensure the compatibility between organisations and  agencies with the centralised database for data sharing and  other accessibility issues.
Keywords: Centralised Database; Distributed Database; Security; Sustainable Development